ANALISIS CAPAIAN HIGHER ORDER THINKING SKILLS (HOTS) ANAK USIA DINI MELALUI PEMBELAJARAN BERBASIS PROJEK - Trivena Dyah Wijayanti (Jurnal Educhild : Pendidikan dan Sosial, 2023)
This study aims to analyze the achievement of Higher Order Order Thinking Skills (HOTS) in early childhood through project-based learning. This research is a qualitative descriptive study. Collecting data using interviews, observation, and documentation. The subjects of this study were class teachers and students at Alam Efata Bersinar Kindergarten, Salatiga City. Data analysis techniques used interactive analysis of the Miles and Huberman models with data reduction steps, data presentation, and drawing conclusions. The results showed that the percentage of children's HOTS achievements while participating in project-based learning was 63.7%. The achievement of skills includes the skills of choosing, organizing, combining, proving, choosing, differentiating, analyzing, creating, combining, finding, collecting, concluding, and categorizing. Furthermore, the application of the guidelines for implementing project learning in early childhood education, as well as teachers' readiness and maturity in preparing project-based learning, supported the HOTS achievements of early childhood in this studyPPenelitian ini bertujuan untuk menganalisis capaian Higher Order Thinking Skills (HOTS) anak usia dini melalui pembelajaran berbasis projek. Penelitian ini merupakan penelitian deskriptif kualitatif. Pengumpulan data menggunakan wawancara, observasi, dokumentasi. Subjek penelitian ini diantara yaitu guru kelas serta peserta didik di TK Alam Efata Bersinar, Kota Salatiga. Teknik analisis data menggunakan analisis interaktif model Miles dan Huberman dengan langkah reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan persentase capaian HOTS anak selama mengikuti pembelajaran berbasis proyek sebesar 63,7%. Capaian keterampilan meliputi keterampilan memilih, mengatur, memadukan, membuktikan, memilih, membedakan, menganalisis, mengkreasikan, menggabungkan, menemukan, mengumpulkan, menyimpulkan dan mengkategorikan. Selain itu capaian HOTS anak usia dini dalam penelitian ini juga juga didukung dengan penerapan metode projek yang sesuai pedoman panduan penyelenggaraan pembelajaran projek di PAUD serta kesiapan dan kematangan guru dalam mempersiapkan pembelajaran berbasis projek